Substansi Prinsip Profesionalisme Dalam Peran Notaris Sebagai Pejabat Umum Terhadap Pembuatan Akta Autentik - Anita Nurjanah (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
According to Article 1 Paragraph (1) of Law Number 30 of 2004, a Notary is a public official authorized to make authentic deeds and other authorities as stipulated in the Law. In carrying out their duties, a Notary is supervised by Article 16 and Article 17 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary. There are no legal sanctions or regulations regarding professionalism in the Law on Notary Positions, even though Notaries often stumble into problems due to negligence or unprofessionalism in carrying out their duties as public officials with authority. Notaries are expected to prioritize professionalism, especially in the making and handling of deeds entrusted to them by clients. However, mistakes or errors can occur in carrying out their duties due to their lack of professionalism, which can have legal consequences for themselves. This study is a normative juridical study using secondary data. The research approach used legal, case, and conceptual approaches using primary, secondary, and tertiary legal materials. The results of the study conclude that Notaries are expected to prioritize professionalism in carrying out their duties so that the public can trust the position of a Notary.